2013
DOI: 10.4103/0973-1482.119358
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin induced flagellate erythema: Revisiting a unique complication

Abstract: Bleomycin induced flagellate dermatitis is a rare and unique adverse effect. With the declining use of bleomycin, this complication is becoming increasingly infrequent in common clinical practice. We herein describe a case of a 22-year-old Indian male with Hodgkin's lymphoma, Ann Arbor stage IIBEX developing flagellate dermatitis following 1(st) cycle of chemotherapy with ABVD regimen. The diagnostic dilemma in the illustrative case underscores the importance of awareness and prompt identification and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 11 publications
0
36
0
4
Order By: Relevance
“…The linear or streaked pigmentation usually develops after a cumulative dose between 100-300 U of bleomycin (6,17), whereas considering our cases the cumulative doses were 38 U and 30 U. There are only 17 adult cases of FH following treatment with low-dose bleomycin (Table 1) (2,4,6,8,9,14,15,(17)(18)(19)(20)(21)(22)(25)(26)(27). It is observed that the majority of patients developing FH within 7 days of administration of bleomycin were young adults, even the dose of bleomycin was between 5-30 U.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The linear or streaked pigmentation usually develops after a cumulative dose between 100-300 U of bleomycin (6,17), whereas considering our cases the cumulative doses were 38 U and 30 U. There are only 17 adult cases of FH following treatment with low-dose bleomycin (Table 1) (2,4,6,8,9,14,15,(17)(18)(19)(20)(21)(22)(25)(26)(27). It is observed that the majority of patients developing FH within 7 days of administration of bleomycin were young adults, even the dose of bleomycin was between 5-30 U.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in the treatment of malignancies such as lymphomas, germ cell tumors, and squamous cell carcinoma (4). At low doses, it inhibits mitosis; however at higher concentrations, it exhibits strong cytostatic activity by blocking the DNA uptake of thymidine in the S-phase of the cell cycle (4,5). Fifty percent of bleomycin is inactivated by an aminohydrolase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations